2018
DOI: 10.1007/978-3-319-93870-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Review of Anthropomorphic Head Stabilisation and Verticality Estimation in Robots

Abstract: In many walking, running, flying, and swimming animals, including mammals, reptiles, and birds, the vestibular system plays a central role for verticality estimation and is often associated with a head stabilisation (in rotation) behaviour. Head stabilisation, in turn, subserves gaze stabilisation, postural control, visual-vestibular information fusion and spatial awareness via the active establishment of a quasi-inertial frame of reference. Head stabilisation helps animals to cope with the computational conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…Head stabilization behavior, which is universally observed in humans and animals, is directly related to the functions of the vestibular system alluded earlier [3]. In humans, experimental studies have shown that the head is stabilized during the performance of different locomoting, balancing, and other postural tasks [4,5].…”
mentioning
confidence: 86%
“…Head stabilization behavior, which is universally observed in humans and animals, is directly related to the functions of the vestibular system alluded earlier [3]. In humans, experimental studies have shown that the head is stabilized during the performance of different locomoting, balancing, and other postural tasks [4,5].…”
mentioning
confidence: 86%
“…Vestibulo-Ocular Reflex (VOR) is the reflex responsible for keeping the gaze stabilized at the current gaze point in space, whereas Optokinetic Reflex (OKR) is the reflex responsible for keeping the gaze on track with the target [1]. Many researches have developed gazing techniques based on HVS to make the robot exhibit a gazing behavior similar to human gaze behavior [2]. It should be noted that gaze control, generally, includes image capturing, image processing, and system control [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the visual stimulus has been analyzed during a car drive to develop a model based on VOR and OKR [22]. Discussion of researches on the topic that address used models, problems and solutions, designs of robots, control methods, and system behavior can be seen in comprehensive reviews, such as [2] and [23].…”
Section: Introductionmentioning
confidence: 99%